Perlindungan Hukum Terhadap Kreditur Atas Upaya Penundaan Lelang Eksekusi Hak Tanggungan Akibat Kredit Macet (Studi Putusan Mahkamah Agung Nomor 15 K/ Pdt/ 2019) - Ade Nona Halawa; Sunarmi Sunarmi; Hasim Purba; Sutiarnoto Sutiarnoto (Iuris Studia: Jurnal Kajian Hukum, 2022)
The provisions for delaying the auction of mortgage executions in the context of settling bad loans have not been regulated in laws and regulations, but only contained in the Joint Statement (PB) and Forced Letter (SP) made by PUPN/KPKNL to postpone the auction of mortgage executions. Legal protection for creditors in the execution of mortgage execution auctions in the context of settlement of bad loans has been provided by Law Number 4 of 1996 concerning Mortgage Rights. Prior to binding the Mortgage Rights, the form of a credit agreement between the creditor and the debtor is prioritized. This Credit Agreement functions as evidence and provides limitations regarding the rights and obligations of each party, so that the credit agreement can guarantee the repayment of creditors' debts, a guarantee binding process must be carried out with a clause granting Mortgage Rights if the object guaranteed is in the form of fixed objects, namely land rights. . Judges' considerations on the Supreme Court Decision Number: 15K/Pdt/2019 in conjunction with the Medan High Court's decision Number 11/Pdt/2018/ PT Medan in conjunction with the Medan District Court's Decision Number 726/Pdt.G/2016/PN-Mdn, Eko Handoko Hasian in terms of This lawsuit filed a lawsuit containing the cancellation of the auction for the execution of the mortgage object, however, the lawsuit filed was not acceptable (Niet Ontvankelijk verklaard) because it considered several things, first the Plaintiff's Lawsuit Contains Premature Disability, and second, the Plaintiff's Claim with Less Parties (Exceptio Pluria Litis Consortium). In addition, Eko Handoko Hasian also incorrectly postulated that the execution of the mortgage right requires fiat execution from the court because Law Number 4 of 1996 concerning Mortgage has given the creditor the right of execution which is obtained by the existence of an executorial title contained in the mortgage certificate